The ambiguity of the term ‘spiritual’ in Hong Kong educational discourse: rhetoric and substance - Ho, Wong Ping (International journal of children's spirituality, 2005)
At the turn of the millennium, the term ‘spiritual’ began to gain more prominence in the educational discourse in Hong Kong, both in official policy documents and in religious schools’ descriptions of their own mission. Addressing each of these two cases in turn, a description of the context in which the increased use of the term has occurred leads on to the question of the extent to which this increased rhetorical emphasis on the spiritual is matched by the actual substance of education policy and the reality of religious education. It is found that the match is much less than perfect, and the reasons for this are explored.